Variations in stakeholders' ecosystem service priorities for managing a marine protected area. (December 2022) - Heck, Nadine; Paytan, Adina; Potts, Donald; Haddad, Brent
Abstract: Marine protected areas (MPA) increasingly focus on integrating ecosystem services in MPA management. Understanding how MPA stakeholders value and depend on marine ecosystem services is therefore important to account for local priorities in conservation design and management, and for identifying how different stakeholder groups might be affected by MPA management decisions. This study investigates the importance of MPA ecosystem services in Monterey Bay, California. We surveyed four marine stakeholders in eight communities to elicit stakeholders' ecosystem service priorities and to identify how socio-economic variables relate to ecosystem service importance. We found that all stakeholder groups rated supporting and regulating services as more important than cultural and provisioning services, suggesting that marine conservation efforts could place more emphasis on protecting ecosystem services that are less easily observed and experienced. Identified differences in the importance of ecosystem services among the four groups demonstrate that stakeholders value marine ecosystems in different ways and thus might be affected differently by management actions that target specific ecosystem services. Differences were particularly evident between recreational and commercial fishers suggesting that these groups have a different understanding of how the MPA contributes to their well-being. We also found that the importance of services that are harder to experience and observe, including supporting and regulating services and the intrinsic value of the MPA, did not correlate with most socio-economic variables indicating that these services are less related to the socio-economic profile of MPA users compared to cultural and provisioning services.